RISK FACTORS AND PREVENTION MEASURES FOR ATHEROSCLEROSIS AMONG YOUNG PEOPLE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Atherosclerosis is one of the most serious and common diseases of the cardiovascular system, characterized by the thickening and hardening of the inner walls of the arteries due to the accumulation of fatty deposits. This process restricts blood flow due to narrowing of the vessels and leads to serious complications such as high blood pressure, heart attacks, peripheral arterial disease, and cerebral hemorrhage or hemorrhage . This article discusses the epidemiological situation of atherosclerosis, risk factors that cause the disease, clinical symptoms, diagnostic methods, treatment methods, preventive measures, and the importance of a healthy lifestyle.